Acetylcholine Delays Atrial Activation to Facilitate Atrial Fibrillation - Bayer, Jason D.; Boukens, Bastiaan J.; Krul, Sébastien P. J.; Roney, Caroline H.; Driessen, Antoine H. G.; Berger, Wouter R.; van den Berg, Nicoline W. E.; Verkerk, Arie O.; Vigmond, Edward J.; Coronel, Ruben; de Groot, Joris R. (Frontiers in Physiology, 2019)
Background Acetylcholine (ACh) shortens action potential duration (APD) in human atria. APD shortening facilitates atrial fibrillation (AF) by reducing the wavelength for reentry. However, the influence of ACh on electrical conduction in human atria and its contribution to AF are unclear, particularly when combined with impaired conduction from interstitial fibrosis. Objective Investigate the effect of ACh effect on human atrial conduction and its role in AF with computational, experimental, and clinical approaches. Methods S1S2 pacing (S1=600ms and S2=variable cycle lengths) was applied to the following human AF computer models: a left atrial appendage (LAA) myocyte to quantify ACh effects on APD, maximum upstroke velocity (Vmax), and resting membrane potential (RMP); a LAA monolayer to quantify ACh conduction effects; and 3) a left atrium (LA) to determine ACh arrhythmogenicity. Heterogeneous ACh and interstitial fibrosis were applied to the monolayer and LA models. To corroborate the simulations, APD and RMP from isolated human atrial myocytes were recorded before and after 0.1 µM ACh. At the tissue level, LAAs from AF patients were optically mapped ex vivo using Di-4-ANEPPS. The difference in total activation time (AT) was determined between AT initially recorded with S1 pacing, and AT recorded during subsequent S1 pacing without (n=6) or with (n=7) 100 µM ACh. Results In LAA myocyte simulations, S1 pacing with 0.1 µM ACh shortened APD by 41 ms, hyperpolarized RMP by 7 mV, and increased Vmax by 27 mV/ms. In human atrial myocytes, 0.1 µM ACh shortened APD by 48 ms, hyperpolarized RMP by 3 mV, and increased Vmax by 6 mV/ms. In LAA monolayer simulations, S1 pacing with ACh hyperpolarized RMP to delay total AT by 32 ms without and 35ms with fibrosis. This led to unidirectional conduction block and sustained reentry in fibrotic LA with heterogeneous ACh during S2 pacing. In AF patient LAAs, S1 pacing with ACh increased total AT from 39.3±26 ms to 71.4±31.2 ms (P=0.036) compared to no change without ACh (56.7±29.3 ms to 50.0±21.9 ms, P=0.140). Conclusions:In fibrotic atria with heterogeneous parasympathetic activation, ACh facilitates AF by shortening APD and slowing conduction to promote unidirectional conduction block and reentry.